Marriage Pattern and Fertility in DKI Jakarta Province - Herartri, Rina; Pebrianti, Reni; Nugroho, Darojad Nurjono Agung (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2022)
Birth rate or fertility is one of the elements playing a role in determining the population number and age structure in an area. To maintain stable population growth, it is necessary to strive for a total fertility rate (TFR) of around 2.1 children per woman. DKI Jakarta Province had reached this condition before the 2000 period. But in the next period, there was an increase ranging from 2.2 - 2.3 children per woman. Fertility is affected by various factors, including marriage patterns and contraception usage. This study aims to determine the effect of marriage patterns on fertility in DKI Jakarta Province by using the concept of fertility decomposition. The data used are the results of the Indonesian Demographic and Health Survey (IDHS) 2002/03 and 2017 with the unit of analysis for women aged 15-49 years. The results showed that there was a slight increase in the effect of the marriage pattern on fertility restrictions, from 14% or preventing 1.89 births in the 2002/03 IDHS to 19% or preventing the occurrence of 2.1 births in the 2017 IDHS. in DKI Jakarta Province by 2.2 children per woman in the 2017 IDHS, although there was a sharp decline in the effect of contraceptive use. It is necessary to study the relationship between the pattern of marriage and the use of contraception because these two variables play an important role in determining the fertility rate in DKI Jakarta Province.